2012
DOI: 10.3758/s13414-012-0396-7
|View full text |Cite
|
Sign up to set email alerts
|

Using response time distributions to examine top-down influences on attentional capture

Abstract: Three experiments examined contingent attentional capture, which is the finding that cuing effects are larger when cues are perceptually similar to a target than when they are dissimilar to the target. This study also analyzed response times (RTs) in terms of the underlying distributions for valid cues and invalid cues. Specifically, an ex-Gaussian analysis and a vincentile analysis examined the influence of top-down attentional control settings on the shift and skew of RT distributions and how the shift and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 48 publications
(71 reference statements)
1
5
0
Order By: Relevance
“…Furthermore, the stronger cueing effects of cues with a color matching that of the searched-for targets than of cues with a color different from the targets were present from the fastest responses onward. This observation is in line with the theory of top-down contingent capture because, according to this theory, participants would set up their attentional control settings in advance, so that each stimulus that matched the setting would have a chance of capturing attention more efficiently from the fastest responses onward (Ansorge & Horstmann, 2007;Burnham, 2013). In the present study, we found no direct support for the deallocation theory, which predicts an increase of the cueing-effect difference between matching and nonmatching cues across time.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Furthermore, the stronger cueing effects of cues with a color matching that of the searched-for targets than of cues with a color different from the targets were present from the fastest responses onward. This observation is in line with the theory of top-down contingent capture because, according to this theory, participants would set up their attentional control settings in advance, so that each stimulus that matched the setting would have a chance of capturing attention more efficiently from the fastest responses onward (Ansorge & Horstmann, 2007;Burnham, 2013). In the present study, we found no direct support for the deallocation theory, which predicts an increase of the cueing-effect difference between matching and nonmatching cues across time.…”
Section: Discussionsupporting
confidence: 81%
“…In any case, the difference between the cueing effects of matching white color cues and of nonmatching red color cues was present from the fastest responses onward. This is also in line with a contingent-capture account, since control settings are assumed to be set up in advance and can therefore effectively determine which stimuli capture attention directly, from stimulus onset onward (Ansorge & Horstmann, 2007;Burnham, 2013). In contrast, positive evidence for more deallocation (Theeuwes, 2010;Theeuwes et al, 2000) with nonmatching cues than with matching cues would have consisted of a significant cueing effect by nonmatching cues in the earliest quintile(s) and its decrement with increasing RTs (as more time would have passed since the initial capture).…”
Section: Discussionmentioning
confidence: 59%
“…In line with the contingent capture view, among the fastest responses, capture effects were restricted to the matching cueing conditions (see Ansorge & Horstmann, 2007;Burnham, 2013). Again, however, it is equally possible that intertrial priming increased the capture effect in the matching conditions.…”
Section: Discussionmentioning
confidence: 67%
“…5D). Ex-Gaussian models have been previously used to understand the source of reaction time changes in psychological tasks (Burnham, 2012; Heathcote et al, 1991). Given that top-down control processes are slower than stimulus driven processes, it has been hypothesized that changes in the exponential component τ are more likely due to alterations in top-down influences (Burnham, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Ex-Gaussian models have been previously used to understand the source of reaction time changes in psychological tasks (Burnham, 2012; Heathcote et al, 1991). Given that top-down control processes are slower than stimulus driven processes, it has been hypothesized that changes in the exponential component τ are more likely due to alterations in top-down influences (Burnham, 2012). This interpretation would be consistent with other evidence suggesting that fatigue specifically affects aspects of tasks and neurophysiological markers of cognitive control (Boksem, Meijman, & Lorist, 2006).…”
Section: Discussionmentioning
confidence: 99%